Urgensi Sertifikasi Syariah bagi Notaris dalam Menangani Akta Perjanjian Pembiayaan di Perbankan Syariah - Nur Asriaty Solichah (JURNAL ILMIAH NUSANTARA, 2025)
This research discusses the urgency of sharia certification for notaries from a legal perspective, particularly in drafting financing agreement deeds in Islamic banking institutions. Within the national legal system, notaries are authorized to prepare authentic deeds as regulated in the Notary Office Law. However, the absence of provisions requiring sharia competence for notaries creates a legal vacuum that may result in the material content of deeds contradicting Islamic legal principles. This study aims to analyze the regulatory need for sharia certification and examine the legal implications arising from the lack of substantive understanding among notaries regarding fiqh muamalah. This normative juridical research employs qualitative analysis of statutory regulations, fatwas, and legal documents. The findings indicate that discrepancies between notarial deeds and sharia principles can lead to legal uncertainty, diminished legitimacy of deeds as evidence, and potential contractual disputes. Therefore, sharia certification is required as a legal instrument to strengthen the Islamic economic legal system and to ensure legal protection for all parties involved in sharia-based financial transactions.